PLEISTOCENE MARINE DEPOSITS OF THE AIGIALIA REGION (N. PELOPONNESUS) - Τρίκολας Κ.; Κοσκερίδου Ε.; Τσουρού Θ.; Ντρίνια Χ.; Αλεξούλη-Λειβαδίτη Α. (Bulletin of the Geological Society of Greece, 2018)
In Aigialia, and in the region of Aigion, after geological mapping, marine deposits of small extent and 3 to 60 m thick were found in altitudes by 30-820 m. These deposits are mainly composed of conglomeratic beds and sands and constitute remnants of marine terraces. In the marine deposits, fossils indicative of a coastal marine environment and age to Pleistocene, were found. The location and the altitude of the marine deposits have direct relation with the neotectonics of normal faults, the altitude of which exceeds 600 m. Based on the stratigraphy and the tectonics of the region, the age of the marine sediments is attributed to the Middle-Late Pleistocene.